أسلوب ضرب الأمثال في الدعوة إلى الله :bدراسة إستقرائية في ضوء القرآن الكريم /cإعداد، نور الحليمة الوراع بنت حاج مؤمين - Nurol Halimatulwara' Haji Mumin (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study analyzes the style of citing al-Amthal (Parables or Proverbs) in calling to Allah, in the light of Glorious al-Qur'an al-Karim. The aim of this research is to explain the concept of al-Amthal al-Qur'aniyyah (Qur'anic Parables) and its importance as one of the fundamental ways and means in the area of calling to Allah. Furthermore it is to know the secrets of al-Amthal al-Qur'an, and explain its relationship to the issues connected with religious faith and social behaviourism. Likewise, it is to expound its role in conveying Islam and spreading sound understanding about the Islamic faith. This study is also discussing the implications and benefits of citing al-Amthal al-Qur'aniyyah in calling to Allah as well as the possibility of using these al-Amthal as a Qur'anic style in conveying Islam in the present time. In order to achieve her goal, the researcher has used the selected al-Amthal contained in the Glorious al-Qur'an, considering that they represent a kind of Divine guidance of God that exhorts the souls on righteousness and distance them from sin and evil, or motivates them towards virtues. It also strives to implant religious values far from deviation, and values that call unto faith in the oneness of Allah and His attribute of absolute perfection. The researcher adopts her study upon analytical, descriptive and inductive methods based on some al-Amthal found in al-Qur'an. The researcher also depends on both old and modern Qur'anic exegesis (tafsir). The researcher has confirmed that style of citing of al-Amthal in the al-Qur'an is one of the most important and best styles that could assist in the spread of Islam across the inhabited parts of the globe, due to the consideration that it is the style, which based on logical induction, comparison and analogy. Similarly, it is also based on an experimental work that rest on approximation of meanings, unraveling the mystery, and understanding what are hidden from sights and hearings. The researcher concluded that the style of citing al-Amthal is also one of the most important means of training minds on discussion, debate, argument, and arriving at the truth through proper thinking.